2020
DOI: 10.1097/ju.0000000000001288
|View full text |Cite
|
Sign up to set email alerts
|

Delaying Cancer Cases in Urology during COVID-19: Review of the Literature

Abstract: Purpose: Coronavirus disease 2019 (COVID-19) is a global pandemic affecting hospital systems and the availability of resources for surgical procedures. Our aim is to provide guidance for urologists to help prioritize urological cancer surgeries. Materials and Methods: We reviewed published literature on bladder cancer, upper tract urothelial carcinoma, penile cancer, testis cancer, prostate cancer, renal cancer and adrenal cancer. Results: For muscle invasive bladder cancer delays should be less than roughly 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
53
1
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 46 publications
(48 reference statements)
3
53
1
3
Order By: Relevance
“…Several articles have provided insight into how practitioners should approach this difficult dilemma accordingly to each cancer histology. Suggestions and guidelines are available for head and neck, sino-nasal, spinal, breast, upper tract urothelial, cervical, penile, testicular, pancreatic, kidney, gastric, colorectal, skin, adrenal, liver, prostate, ovarian, endometrial, bladder and endocrine cancer ( Cohen et al, 2020 ; Baumann et al, 2020 ; Werner et al, 2020 ; Tarantola et al, 2013 ; Catanese et al, 2020 ; Vecchione et al, 2020 ; Turri-Zanoni et al, 2020 ; de C. Zequi and Abreu, 2020 ; Gravas et al, 2020 ; O’Leary et al, 2020 ; Casco et al, 2020 ; Katims et al, 2020 ; Berjano et al, 2020 ; Kapuria et al, 2020 ; P. March 25 and 2020, 2021 ; Tachibana et al, 2020 ; Loveday et al, 2020 ; Jones et al, 2020 ; Villani et al, 2020 ; Fligor et al, 2020 ; Sanchez et al, 2020 ; Wallis et al, 2020 ; Topf et al, 2020 ; Matsuo et al, 2020 ; Colombo et al, 2020 ; Campi et al, 2020 ; Raghavan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several articles have provided insight into how practitioners should approach this difficult dilemma accordingly to each cancer histology. Suggestions and guidelines are available for head and neck, sino-nasal, spinal, breast, upper tract urothelial, cervical, penile, testicular, pancreatic, kidney, gastric, colorectal, skin, adrenal, liver, prostate, ovarian, endometrial, bladder and endocrine cancer ( Cohen et al, 2020 ; Baumann et al, 2020 ; Werner et al, 2020 ; Tarantola et al, 2013 ; Catanese et al, 2020 ; Vecchione et al, 2020 ; Turri-Zanoni et al, 2020 ; de C. Zequi and Abreu, 2020 ; Gravas et al, 2020 ; O’Leary et al, 2020 ; Casco et al, 2020 ; Katims et al, 2020 ; Berjano et al, 2020 ; Kapuria et al, 2020 ; P. March 25 and 2020, 2021 ; Tachibana et al, 2020 ; Loveday et al, 2020 ; Jones et al, 2020 ; Villani et al, 2020 ; Fligor et al, 2020 ; Sanchez et al, 2020 ; Wallis et al, 2020 ; Topf et al, 2020 ; Matsuo et al, 2020 ; Colombo et al, 2020 ; Campi et al, 2020 ; Raghavan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that COVID-19 is a highly contagious disease that can cause respiratory problems that may require intensive care and ventilator support and can result in death. In the period of COVID-19, due to epidemiological factors and high hospitalizations, elective surgeries were canceled and emergency and oncological surgical procedures were prioritized in order to maintain the capacity of health systems to meet expected cases and to avoid unnecessary exposure to COVID-19 6 . However, despite this priority, some oncology patients have delayed or completely canceled their treatment during the pandemic process.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it was reported that cancer treatment services were partially or completely interrupted in 42% of the 155 countries examined by WHO 7,8 . COVID-19 has also significantly changed the management of urological cancers 6 . It is known that delay in surgical intervention in MIBC, which is one of the urological cancers, significantly reduces the life expectancy of the patient 9,10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prognose zu rechnen ist, gibt es beim in-vasiven Urothelkarzinom der Blase und des oberen Harntrakts Untersuchungen, die zeigen, dass eine Aufschiebung der Zystektomie oder Nephroureterektomie mit einer Verschlechterung des Gesamtüberlebens einhergeht. Bei anderen Tumoren wie dem Prostatakarzinom kann durch eine Androgendeprivation ein längeres Intervall bis zu einer Operation erreicht werden[6].Urologe https://doi.org/10.1007/s00120-021-01451-6 © Springer Medizin Verlag GmbH, ein Teil von Springer Nature 2021…”
unclassified